Studi Kasus Penegakan Kedisiplinan Lingkungan Siswa SD Negeri 1 Kota Bengkulu - Ita Yulianingsih; Bambang Parmadie; Feri Noperman (Universitas Bengkulu, 2020)
This study aims to know the discipline of the SD Negeri 1 Bengkulu City. The research method used is that, quantitative description. The source of the date ini this study is a direct observation of studentd about discipline in schools with study subjects is teachers and students and additional date that comes from written sources, documentation, book and so on. The date collection techniques used are observation, interviews and documentation, using date analysis techniques for date condensation, presentation date and summary withdrawal. Based on the research conducted by the researchers, the enforcement of discipline at the SD Negeri 1 Bengkulu City was not only about attendance or lack of attendance, being late or not. It refers to the establishment of an environment in which there are rules or common orders that must be respenceted in school aplly the various elements of discipline such as rules, disciplinary habists, awards and exemplary giving to discipline students.